2022
DOI: 10.3390/molecules27175665
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Analysis of Acinetobacter baumannii Strain AB43 Containing a Type I-Fb CRISPR-Cas System: Insights into the Relationship with Drug Resistance

Abstract: The CRISPR-Cas system is a bacterial and archaea adaptive immune system and is a newly recognized mechanism for controlling antibiotic resistance gene transfer. Acinetobacter baumannii (A. baumannii) is an important organism responsible for a variety of nosocomial infections. A. baumannii infections have become problematic worldwide because of the resistance of A. baumannii to multiple antibiotics. Thus, it is clinically significant to explore the relationship between the CRISPR-Cas system and drug resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The relationship between drug resistance and the CRISPR-Cas system was analyzed in A. baumannii strain AB43 using the whole-genome sequencing (WGS) technique [ 362 ]. The authors identified the presence of the Type I-Fb CRISPR-Cas system in the strain AB43 and found that the cas gene in the studied strain has a higher similarity index with the similar subtype cas genes.…”
Section: Importance Of Crispr-cas Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between drug resistance and the CRISPR-Cas system was analyzed in A. baumannii strain AB43 using the whole-genome sequencing (WGS) technique [ 362 ]. The authors identified the presence of the Type I-Fb CRISPR-Cas system in the strain AB43 and found that the cas gene in the studied strain has a higher similarity index with the similar subtype cas genes.…”
Section: Importance Of Crispr-cas Systemmentioning
confidence: 99%
“…However, no matches for CRISPR spacers were found for AMR genes for A. baumannii strain AB43. The drug resistance mechanism in A. baumannii strain AB43 via the CRISPR-Cas system is still unclear, as the endogenous CRISPR-Cas system might be responsible for inhibition of drug resistance gene expression, which requires further research [ 342 , 362 ]. Another study using WGS identified the CRISPR-Cas system Subtype I-F in A. baumannii strain ATCC BAA1605, with a high number of spacers present in the CRISPR loci [ 363 ].…”
Section: Importance Of Crispr-cas Systemmentioning
confidence: 99%
“…Due to its robust survival capabilities, A. baumannii , a non-fermenting Gram-negative bacterium ( De Silva and Kumar, 2019 ; Muller et al, 2023 ) has become the most common source of hospital-acquired infections such as ventilator-associated pneumonia, bloodstream infections, and urinary tract infections ( Guo et al, 2022 ; Cavallo et al, 2023 ). Over the years, owing to the widespread use of antibiotics, the resistance rate of A. baumannii is continually increasing ( Peleg et al, 2008 ; Castillo-Ramirez, 2023 ), making it one of the most critical bacteria for which new antibiotics are urgently needed, as declared by the World Health Organization ( Boucher et al, 2009 ; Tacconelli et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with the rising rates of antibiotic resistance, there is an urgent need to explore alternative approaches to prevent resistance. The clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein (CRISPR-Cas) system is a remarkable immune system in prokaryotes that provides adaptive immunity against foreign genetic elements ( Kao et al, 2021 ; Mortensen et al, 2021 ), such as bacteriophages and plasmids ( Li et al, 2016 ; Guo et al, 2022 ). The CRISPR-Cas system has been classified into two categories, with six types (I-VI) and over 30 subtypes based on the composition of effector complexes ( Huang and Zhu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation